Odpowiedź :
1) x-13=4
x-13+13=4+13
x=4+13
x=17
2) y•7=63
7y=63
7y/7 = 63/7
y=9
3) -2x+13=1
-2x-13+13=1+13
-2x=14
-2x/-2 = 14/-2
x=-7
4) 9+0,5x=10
0,5x=10-9
0,5x=1
x=2
x-13+13=4+13
x=4+13
x=17
2) y•7=63
7y=63
7y/7 = 63/7
y=9
3) -2x+13=1
-2x-13+13=1+13
-2x=14
-2x/-2 = 14/-2
x=-7
4) 9+0,5x=10
0,5x=10-9
0,5x=1
x=2
Odpowiedź:
[tex]1)\\\\x-13=4\\\\x=4+13\\\\x=17\\\\\\Spr.\\\\L=17-13=4\\\\P=4\\\\L=P\\\\\\2)\\\\y*7=63\\\\7y=63\ \ |:7\\\\y=9\\\\\\Spr.\\\\L=9*7=63\\\\P=63\\\\L=P[/tex]
[tex]3)\\\\-2x-13=1\\\\-2x=1+13\\\\-2x=14\ \ |:(-2)\\\\x=-7\\\\\\Spr.\\\\L=-2*(-7)-13=14-13=1\\\\P=1\\\\L=P\\\\\\4)\\\\9+0,5x=10\\\\0,5x=10-9\\\\0,5x=1\ \ |:0,5\\\\x=2\\\\\\Spr.\\\\L=9+0,5*2=9+1=10\\\\P=10\\\\L=P[/tex]